RENIN-ANGIOTENSIN SYSTEM INHIBITION, CARDIORESPIRATORY FITNESS AND MORTALITY RISK IN DIABETIC PATIENTS. (April 2021) - Pittaras, Andreas; Grassos, Haralampos; Doumas, Michael; Myers, Jonathan; Faselis, Charles; Kokkinos, Peter
Abstract : Objective: Patients with type 2 diabetes mellitus (T2DM) have significantly higher risk of cardiovascular events and mortality. Angiotensin-converting enzyme inhibitors (ACEI) and angiotensin receptor blockers (ARBs) decrease mortality risk in T2DM patients. Cardiorespiratory fitness (CRF) is associated with lower mortality risk in T2DM patients. However, the combined effects of CRF and ACEI/ARBs on mortality risk in T2DM patients has not been assessed. Design and method: We identified 6, 888 T2DM patients (age 58.3 + 10.1 years) with no evidence of ischemia as indicated by a maximal standardized exercise treadmill test. We established two CRF categories based on age-adjusted median peak metabolic equivalents (METs) achieved: Unfit (5.4 ± 1.3 METs; n = 3, 474) and Fit (9.0 ± 2.3 METs; n = 3414). We then formed 2 groups within each CRF category (treated and not treated with ACEI/ARBs) for a total of four CRF-ACEI/ARBs groups. Cox proportional hazards models, adjusted for known risk factors were constructed to assess the CRF-ACEI/ARBs interaction and mortality risk association. Results: During a follow-up of 14.2 + 6.9 years, 2, 495 patients died, accounting for 25.5 events/ 1, 000 person-years of observation. Patients treated with ACE/ARBs had 25% lower mortality risk compared to those not treated with ACE/ARBs (HR 0.75; 95% CI: 0.69-0.82). When CRF-ACEI/ARBs categories were considered, Unfit individuals not treated with ACEI/ARBs had 24% higher mortality risk compared to those treated with ACEI/ARBs (HR 1.24; 95% CI 1.11–1.38). For Fit individuals, the risk was 26% lower (HR: 0.74; CI: 0.66–0.83) for those not treated with ACEI/ARBs and 45% lower in those treated with ACEI/ARBs (HR 0.55; 95% CI 0.48–0.62). Conclusions: ACEI/ARBs therapy and increased CRF are effective in lowering mortality risk in in T2DM patients. The combination of ACEI/ARBs and higher CRF was synergistic, resulting in substantially lower mortality risk than either therapy alone.